(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The aim of the present work is to propose and substantiate a scheme of a device for positioning prismatic-body details on two holes with parallel axes and a plane, perpendicular to them. This will help to achieve high accuracy of linear and angular orientation of the workpiece. Thus the requirements for the accuracy of the center-to-center distance of the base holes will be reduced and the process of assembling the workpiece to the grip pawls will be simplified.